The Readiness of SMEs in Bulungan to Face ASEAN Economic Community (AEC) - Nurus Soimah (Jurnal Ekonomi dan Studi Pembangunan, 2017)
ASEAN Economic Community (AEC) is formed on the basis of an agreement in order to create a relationship of closer cooperation among ASEAN countries. The agreement covers four strategic, namely: (1) the achievement of a single market and a unified production base, (2) a competitive economic region, (3) equitable economic growth, and (4) integrated with the global economy. This research aimed to identify the readiness of SMEs Facing the ASEAN Economic Community (AEC), which will begin to be realized in December 2015. This research is a qualitative descriptive research. The researcher took a case study on SMEs in Bulungan Regency by selecting informants by using Purposive Sampling. 36 SMEs domiciled in Bulungan Regency were taken as the research subject. The data used in this research was a combination of primary data obtained in the field through interviews and secondary data adapted from various sources as a reference for research writing. Data analysis techniques used was data reduction and validity techniques using triangulation. The result of the research shows that the problem of SMEs in Bulungan Regency is the problem of the production process, capital, marketing, and permit. Further research results indicate that Bulungan Regency Government has been trying to encourage the development of the SMEs, but the implementation of government policy is not maximized. Based on the conditions and problems faced by SMEs in Bulungan Regency, it is not ready to face the AEC.Keywords: Readiness, SMEs, MSEs, ASEAN Economic Community (AEC)JEL Classification: G10, G20